Mechanical Properties And Cutting Performance Of Electroless Ternary Ni-W-P Coated Cutting Tools. - Md Ali, Mohd Amran; Abdul Aziz, Mohd Sanusi; Redzuwan, Bahrin Ikram; Muhammad Zaimi, Zainal Abidin; Raja Abdullah, Raja Izamshah; Kasim, Mohd Shahir; Mizobuchi, Akira; Ishida, Tohru (Universiti Teknologi Malaysia, 2017)
This paper presents a new approach of electroless nickel deposition (END) on cutting tools as to enhance tool performance. END involves several reactions in aqueous solution and is performed without using electrical power. The cutting performance of electroless ternary Ni-W-P alloy-coated cutting tools that were prepared in plating baths with different pH levels and with the addition of heat treatment was investigated. The cutting tool life was evaluated during machining on AISI D2 steel followed by measurement of surface roughness. Experimental results showed that END cutting tools produced from a plating bath with a pH of 8.5 with heat treatment resulted in the longest tool life, which was 7 minutes 32 seconds, and the lowest surface roughness, which was 0.412 μm. High deposition rate and high thickness of coating obtained under such pH condition were found to be the main factors in enhancing tool life. Furthermore, the addition of heat treatment increases the hardness and improves the coating surface.